ST-Segment Elevation Myocardial Infarction Related to Potential Spontaneous Coronary Thrombosis in Pheochromocytoma Crisis - Chen, Fei; Zheng, Mingxia; Li, Xi; Peng, Yong; Chen, Mao (Frontiers in Endocrinology, 2020)
Pheochromocytoma crisis is a rare and possibly fatal emergency. Hypersecreted catecholamines may result in myocardial injury via its direct toxic effect on cardiomyocytes or mediating vasoconstriction which will reduce coronary blood flow in this special setting. Interestingly, several case studies have reported the occurrence of ST-segment elevation myocardial infarction in patients with pheochromocytoma crisis. However, no one found the angiographic evidence of occlusive thrombus in the infarct-related coronary artery. Additionally, pheochromocytoma can induce hypercoagulability and promote thrombosis, but spontaneous coronary thrombosis has never been reported in this condition. Here, we report an unusual case of pheochromocytoma crisis presenting with STEMI due to spontaneous coronary thrombosis.